Characterization of N-acetylglucosaminidase gene from aureus / Khalida Ain Kusnan - Kusnan, Khalida Ain (2014)
SACOL2666, which is known as an N-acetylmuramoyl-L-alanine in NCBI database is shown to be homologuos with atl of S. aureus, a bifunctional autolysin gene. In this study, in-silico analysis of deduced amino acids sequence SACOL2666 was characterized to confirm the protein from S. aureus SHI000 is an Nacetylglucosaminidase autolysin. Successful transformed gene in pBAD-sScaB and pQE60-xScaQ clones contain 1860 bp of the full gene and 1779 bp of gene without signal peptide sequence. An N-acetylglucosaminidase protein family (PF01832) of Lysozyme like superfamily is found in SACOL2666 domain architecture. The amino acid of SACOL2666 gene demonstrated a high sequence similarity to characterized N-acetylglucosaminidases, AcmB (L. lactis) and Auto (L. monocytogenes) Group B in GH73 rather than bifunctional autolysins in Group A, Atl (S. aureus). SACOL2666 has high relatedness in sequence similarity (46%) and structural alignment with N-acetylglucosaminidases Auto Chain A structure (3FI7 A). Residue E352, G356, E386, F399, Y455 and a tetrad YATD (Y449-D452) at SACOL2666 hypothetical secondary structures are shown to be identical to Auto (3FI7_A) residues. As conclusion, this study reveals SACOL2666 as a novel N-acetylglucosaminidase with high sequence similarity to N-acetylglucosaminidases in Group B of GH73. Moreover, structural similarity suggests the functional and enzymatic activity of SACOL2666 is similar to Auto (3FI7 A).